Gradually Increased Training Intensity Benefits Rehabilitation Outcome after Stroke by BDNF Upregulation and Stress Suppression. (19th June 2014) - Sun, Jing; Ke, Zheng; Yip, Shea Ping; Hu, Xiao-ling; Zheng, Xiao-xiang; Tong, Kai-yu
Abstract : Physical training is necessary for effective rehabilitation in the early poststroke period. Animal studies commonly use fixed training intensity throughout rehabilitation and without adapting it to the animals' recovered motor ability. This study investigated the correlation between training intensity and rehabilitation efficacy by using a focal ischemic stroke rat model. Eighty male Sprague-Dawley rats were induced with middle cerebral artery occlusion/reperfusion surgery. Sixty rats with successful stroke were then randomly assigned into four groups: control (CG, n = 15 ), low intensity (LG, n = 15 ), gradually increased intensity (GIG, n = 15 ), and high intensity (HG, n = 15 ). Behavioral tests were conducted daily to evaluate motor function recovery. Stress level and neural recovery were evaluated via plasma corticosterone and brain-derived neurotrophic factor (BDNF) concentration, respectively. GIG rats significantly (P < 0.05 ) recovered motor function and produced higher hippocampal BDNF (112.87 ± 25.18 ng/g). GIG and LG rats exhibited similar stress levels (540.63 ± 117.40 nM/L and 508.07 ± 161.30 nM/L, resp.), which were significantly lower (P < 0.05 ) than that (716.90 ± 156.48 nM/L) of HG rats. Training with gradually increased intensity achieved better recovery with lower stress. Our observations indicate that a training protocol that includes gradually increasing training intensity should be considered in both animal and clinical studies for better stroke recovery.